Characteristics of Acute Otitis Media Patients at The Citra Medan Perjuangan Clinic in 2020 - Annisa Lismarani; Dewi Ratnasari; Azwar Ridwan (The Faculty of Veterinary Medicine of Syiah Kuala University, 2021)
Otitis media is inflammation of part or all of the middle ear mucosa, Eustachian tube, mastoid antrum, and mastoid cells. Otitis media is less common in adults than in children and is more common in men. The clinical symptoms of AOM depend on the stage of the disease and the age of the patient. The purpose of this study was to determine the characteristics of patients with acute otitis media in the field of battle image clinic in 2020 based on gender, age, and clinical symptoms. This research was conducted by collecting data from medical records at the citra medan perjuangan clinic in 2020. Then the data was processed using a computer, and the results were analyzed descriptively by univariate analysis. The number of samples that have been collected is 72 people. The highest distribution was male sex at 61.1%, age 1-5 years at 61.1%, and fever at 58.3%. Further research is needed to determine the risk factors for AOM that can be used as prevention.